Roofline: An Insightful Visual Performance Model for Multicore Architectures. - Williams, Samuel; Waterman, Andrew; Patterson, David (Communications of the ACM, 2009)
The article discusses computer architecture design related to multicore microprocessors, examining a visual performance model proposed by the authors called Roofline. Microprocessors will become more diverse, the article indicates, as no conventional wisdom has emerged concerning their design. Topics include demonstrating Roofline on four diverse multicore computers using four key floating-point kernels, highlighting and and quantifying the critical influence of a system bottleneck, and relating processor performance to off-chip memory traffic.